Mulheres agricultoras familiares na assistência técnica e extensão rural: alcances e limites - Costa, Edimare Ribeiro (2018)
This work identifies the ATER intervention strategies developed in the services provided by COOPERA, in the Public Call of 2012 and 2015, in three municipalities of the Northern Coastal Territory and Agreste Baiano from the actions that contemplate the gender relations. Its general objective is to analyze the difficulties of the technicians to work on the specific issues of women farmers in this public policy. This study also aims to describe the genesis and functioning of PNATER, as well as to investigate the methodological approaches of gender worked by the technicians. This is a qualitative research, in which a case study is carried out at COOPERA, using semi-structured interviews and documentary analysis. The analyzes from the field work reveal that the methodological orientations used by the ATER team focus on the productive aspects and do not incorporate gender relations. Thus, there is a need to include specific actions for women and gender training for technicians. However, even with all these limits and difficulties the women interviewed report improvements in their lives after ATER.